Caracterização de pacientes com obesidade candidatos à cirurgia bariátrica - Liberatore, Sabrina Fernandes (2017)
Obesity is a chronic, multifactorial disease that involves psychological, genetic and environmental issues. Studies have been conducted to analyze the psychological profile of the patient who will undergo bariatric surgery. Objective: To characterize obesity patients, candidates for bariatric surgery and to identify lifestyle and the presence of symptoms of anxiety, depression and binge eating. Method: A retrospective study was carried out based on data from patients' charts in a private clinic in the interior of São Paulo, who were candidates for bariatric surgery, evaluated by psychology between January 2010 and December 2015. The psychological evaluation included a data questionnaire (BMI), the Beck Anxiety Inventory (BAI), the Beck Depression Inventory (BDI) and the Periodic Feed Compulsion Scale (ECAP). Results: 188 medical records were analyzed. Age ranged from 16 to 65 years (mean 34.7; SD: 11.3), 73% (n = 137) were female, 48.4% (n = 91) were married, and BMI ranged from 30 to 67 (mean 42.8; dp: 6.5). The BAI results indicated that 53% (n = 100) had minimal anxiety symptoms; of BDI that 52% (n = 97) presented symptoms of mild to severe depression; and ECAP, that 26% (n = 50) presented binge eating. Conclusion: Most of the patients were female, sedentary, young adults, with a history of family obesity and childhood obesity onset. Arterial Hypertension was the most common comorbidity among participants. Symptoms of anxiety and depression were present as well as binge eating.